Removal of Boundary Markers on Sebatik Island: Legal Implications for Regional Sovereignty and Protection of Border Communities - Titaley, Gracio Sulistyo; Wattimena, Josina Augustina Yvonne; Leatemia, Wilshen (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Borders represent a manifestation of state sovereignty. The relocation of boundary markers between Indonesia and Malaysia on Sebatik Island without formal agreement violates international law. Such actions may alter legally recognized territorial boundaries and thus constitute a breach of sovereignty, potentially leading to serious legal implications.Purposes of the Research: The purpose of this study is to analyze the legal consequences of relocating boundary markers between nations, particularly between Indonesia and Malaysia on Sebatik Island. It also examines the implications for territorial sovereignty, bilateral relations, and the provisions of international law governing officially recognized and binding state borders.Methods of the Research: This research is a normative legal research “legal research